The impact of financial services globalisation on islamic and conventional bank performance in GCC and MENA countries (2017)
Empirical researches have shown that Islamic banks were more efficient than the conventional banks before, during and after global financial crises and were more resilient to negative profitability and speculation commonly identified with conventional banks despite that the former have grown as a result of globalisation of financial markets, product innovation, and delimitation of financial regulations, among others. However, the analyses of globalisation or internationalisation of financial services have concentrated only on the cross-border flow of portfolio investment in country stock markets, ignoring foreign direct investment and movement of financial services professionals. Using panel regressions to analyse the impact of financial services globalisation, the paper finds that net capital account used to measure the phenomenon has no significant impact on Islamic banks’ performance measured in terms of return on equity, return on asset and profit before tax. This may be due to the oft-cited limited patronage for Islamic banking in general. The policy implication suggests the need for an increased drive to popularise Islamic banking products in non-Islamic countries and for Islamic banks to more actively engage in cross-border trade of Islamic banking services, as well as foreign direct investment in subsidiary banks outside their traditional locations.